PRINSIP KOMUNIKASI YANG BAIK MENURUT DOKUMEN ETIKA DALAM KOMUNIKASI - Klau, Adelina Bete; Loce, Feronika Jenifer; Mayabubun, Thadeo Devis; Pangalila, Jufaldo (Pineleng Theological Review, 2024)
The article explored the meaning of effective communication according to the ethical principles outlined in the document "Ethics in Communication." It examined various ethical principles that underlie communication practices and attempts to answer the research question: How can one communicate effectively according to the principles outlined in the document "Ethics in Communication"? Through a comprehensive analysis of these principles, coupled with empirical evidence and a theoretical framework, this article aims to provide insight into strategies and approaches for achieving ethical and effective communication. By highlighting the relationship between ethics and communication excellence, this article contributes to the advancement of ethical communication practices in diverse contexts.